(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
The topic of national and cultural specifics is quite traditional for research in the field of phraseology. For many years, works on phraseology (especially if they were carried out within the framework of traditional linguistics) argued that phraseological units are nationally specific units of the language that accumulate the cultural potential of the people.